2013
DOI: 10.17159/2413-3108/2013/v25i4a337
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ knowledge of pain: A cross-sectional correlational study of members of the South African Sports and Orthopaedic Manipulative Special Interest Groups

Abstract: Background. Pain is the most common complaint for which patients seek the help of a physiotherapist. Furthermore, pain has been identified as the fifth vital sign, indicating the attention with which physiotherapists should be assessing pain. Previous studies have found deficits in pain knowledge among healthcare providers. Poor knowledge about pain is recognised to lead to poor assessment ability, and subsequently, to poor pain management.Objective. To investigate the pain knowledge of sports and orthopaedic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 14 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…The low response rate (13.3%) limits the generalisability of the survey results, however, the response rate was similar to another survey conducted amongst SASP special interest groups and higher than other online surveys conducted amongst physiotherapists (Clenzos, Naidoo & Parker 2013;Silva, Costa & Costa 2015;Struyf et al 2012). Respondent bias is also a limitation of our study, because physiotherapists who were more knowledgeable about NMD may have been more likely to complete the survey.…”
Section: Section D: Respiratory Management Strategies Used By South African Physiotherapists 6 Months Prior To the Survey (N = 6)mentioning
confidence: 67%
“…The low response rate (13.3%) limits the generalisability of the survey results, however, the response rate was similar to another survey conducted amongst SASP special interest groups and higher than other online surveys conducted amongst physiotherapists (Clenzos, Naidoo & Parker 2013;Silva, Costa & Costa 2015;Struyf et al 2012). Respondent bias is also a limitation of our study, because physiotherapists who were more knowledgeable about NMD may have been more likely to complete the survey.…”
Section: Section D: Respiratory Management Strategies Used By South African Physiotherapists 6 Months Prior To the Survey (N = 6)mentioning
confidence: 67%
“…A similar study amongst South African sports physiotherapists, where the same data collection instrument, the MPKAQ, was used, found that 85.5% of the responding physiotherapists had inadequate pain knowledge and attitudes (scored < 75%), with a mean score of 65.5%. 28 The lowest scores obtained were for the sections on Assessment and Measurement (47.7%) and Developmental Changes in pain (58.84%). 21 The authors noted that students who studied in their first language scored significantly higher in the physiology section than those who were studying in their second language.…”
Section: Discussionmentioning
confidence: 91%
“…21 The authors noted that students who studied in their first language scored significantly higher in the physiology section than those who were studying in their second language. 28 This highlights the importance of teaching students in their first language yielding a better understanding of the subject. At UCT, English is the medium of instruction, with the possibility that the majority of students are studying in their second language.…”
Section: Discussionmentioning
confidence: 99%
“…A Kenyan study by Jin (2015) (n = 96), which evaluated 'the knowledge and attitudes of various healthcare workers regarding pain assessment and management in children' in the country's national referral hospital, found a significant knowledge gap amongst participants with over half (58.3%) performing poorly, whilst an Ugandan study by Kizza et al (2016) found that 73.5% of clinicians were perceived to have inadequate knowledge in key concepts of pain management. Furthermore, a South African study by Clenzos et al (2016) found only 14.5% of participants with adequate knowledge.…”
Section: Discussionmentioning
confidence: 98%
“…The revised Pain Knowledge and Attitude Questionnaire (RPKAQ) and a section adopted from the Knowledge and Attitudes Survey regarding Pain (KASRP) questionnaire, which mainly focuses on pharmacological management of pain was used to collect data. Both the RPKAQ and KASRP questionnaires have undergone cognitive testing and validation in different settings and cultures and have been found to be reliable (Cronbach's alpha of 0.65 and 0.80, respectively); (Clenzos et al 2016;Ferrell & McCaffery 2012).…”
Section: Data Collection Toolmentioning
confidence: 99%